Pola Penggunaan Media Sosial Masyarakat Desa Bligo, Kecamatan Ngluwar, Kabupaten Magelang, Jawa Tengah - Sudarman Sudarman (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2024)
The aim of this research is to describe the social media usage patterns of the Bligo Village community. Social media is a communication medium that is widely used by the public. With various features and applications that continue to grow, making this social media one of the mainstay media for people around the world., in which from this social media the world economy, and even communication becomes very easy, with the various advantages that this media has. Behind all the conveniences offered by the media, making social media an inseparable part of society, both urban and rural communities. The ease of accessing social media among this community, makes people waste a lot of their time, since they have got addicted in accessing social media content. This research employed descriptive qualitative research method, which describes the current conditions. Then, the research results state that the pattern of social media usage of the Bligo village community, does not show excessive use of social media and is still a necessity, with a pattern of using one to two hours during the day and night, and only a small portion that utilizes more than 4 (four) hours each day. In terms of application usage, WhatsApp application is the first choice before TikTok. In terms of media content patterns, news information becomes community consumption, and religion content becomes the choice of Bligo village community.